The role of strategic planning in achieving organizational agility - Abbas Hussain, Sahar; Hammadi Jaber, Mohammed (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to assess the role of strategic planning in achieving organizational agility at the University of Maysan, as well as the Determining the nature of the relationship between strategic planning and organizational agility represented by the dimensions (response, ability, flexibility, speed) and the model proposed by (Sharifi & Zhang 1999 :17) was used as a measure for the organizational agility variable, which obtained the highest citation rate of 1273, as the research problem embodied By raising a set of questions ,the purpose of which was to clearly diagnose the problem of the research and what is going on around it, and one of the most important of these questions, which represents the main problem of the research, is what is the role of strategic planning in achieving organizational agility at the university. To find out the level of strategic planning application and its role in achieving organizational agility for the university. The sample included (166) administrative staff at the university. It includes all faculty members who held leadership positions in the university’s organizational structure and adopted a number of statistical methods and tools such as percentage, normal distribution and primitive stability according to modeling. Structure, reliability, correlation coefficient, arithmetic mean and frequencies, as well as the adoption of test 2 that shows the role of strategic planning in Achieving organizational agility. The University of Maysan was specifically chosen because the researcher is one of its employees and he found through his experience of the university's reality that it does not have organizational agility, which prompted him to conduct this research. The research found that the university administration has focused on strategic planning and its organization and the scope of benefiting from it in achieving organizational agility and getting rid of career slack and the ability to sense changes in the educational environment and respond to them in a more efficient and superior manner.